Assessment of the load carrying performance of composite cross joints. (May 2020) - Liu, Liyang; Cai, Mengfei; Geng, Xiaoliang; Wang, Peiyan; Yue, Zhufeng
Composite cross joints are common structures in an airframe. When this type of joint is used on an air inlet stiffened structure, it will undertake large bending moment, especially under overpressure of the engine. In this paper, two types of cross joints are tested experimentally and simulated to investigate the load bearing characteristics and make comparative remarks. Four-point bending tests are conducted and the load deflection curves are obtained; besides, the damage pattern of the joints is reported. Based on composite progressive damage model, the numerical simulations have a good agreement with experimental results, revealing the joint failure mechanism and fastener force feature of various joints. The comparative assessment of two types of joints is summarized.